Food photography training with natural light concept using smartphone at SMKN 2 Cirebon City - Kusnadi Kusnadi; Ine Rachmawati; Suhadi Parman; Abdun Wijaya; Rifqi Fahrudin; Marsani Asfi; Sobi Mutohari; Dewi Iriani; Yuni Awalaturrohmah Solihah; Sudadi Pranata (Universitas Muhammadiyah Magelang, 2022)
SMKN 2 Cirebon City's culinary classes produce a variety of food products. However, these products are just displayed and evaluated, though. Therefore, this community service's goal is to improve students' smartphone photography skills as well as their knowledge of photography that makes use of natural light. The method of implementing this program is consultation and training. The program's outcomes include improved smartphone usage abilities and an increase in students' knowledge of photography using natural light to capture images of their learning-based culinary creations.